2013
DOI: 10.4103/0019-5049.118563
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study in the post-operative spine surgeries: Epidural ropivacaine with dexmedetomidine and ropivacaine with clonidine for post-operative analgesia

Abstract: Background:Anaesthesia for spine surgeries is not only concerned with relieving pain during surgeries but also during the post-operative period. A prospective randomised study was carried out to evaluate the efficacy of epidural route and to compare the efficacy and clinical profile of dexmedetomidine and clonidine as an adjuvant to ropivacaine, in epidural analgesia with special emphasis on their quality of analgesia and the ability to provide the smooth post-operative course.Methods:A total of 60 subjects, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…Results of our study showed that total duration of sensory block was significantly longer in group DR as compared to group FR being 413.33 ± 66.71 minutes & 354.66 ± 66.88 minutes respectively. Sensory and motor levels onset, regression and total duration observed in our study were almost similar with studies done by Bajwa et al, Salgado et al, Saravanababu et al and Christelis N et al [9][10][11][12][13] Group FR…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results of our study showed that total duration of sensory block was significantly longer in group DR as compared to group FR being 413.33 ± 66.71 minutes & 354.66 ± 66.88 minutes respectively. Sensory and motor levels onset, regression and total duration observed in our study were almost similar with studies done by Bajwa et al, Salgado et al, Saravanababu et al and Christelis N et al [9][10][11][12][13] Group FR…”
Section: Discussionsupporting
confidence: 92%
“…This result is corroborated by many other authors. [9][10][11][12][13] Onset of attainment of modified Bromage scale III was significantly faster in group DR than group FR. Median value for highest sensory dermatomal level achieved in group DR was T3, being present in 40% patients whereas none of the patients in group FR achieved value of T3 [Table 3, Figure 1].…”
Section: Discussionmentioning
confidence: 99%
“…Clonidine, an imidazoline with selective partial agonist activity at α-2 adrenergic receptors has been used for many years as a centrally acting antihypertensive agent and has also been used as an adjuvant with ropivacaine for regional anaesthesia including epidural anaesthesia. [ 5 6 ] The use of α-2 adrenoceptor agonist for enhancement of peripheral nerve blocks has added a new dimension to their clinical application. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Anterior Cruciate Ligament (ACL) is injured in athletes and trauma victims ( 3 , 4 ). The exact incidence rate of ACL rupture is unknown, and it is best repaired via arthroscopy (3).…”
Section: Introductionmentioning
confidence: 99%
“…The exact incidence rate of ACL rupture is unknown, and it is best repaired via arthroscopy (3). The optimal anesthesia technique for this procedure is the regional anesthesia technique ( 4 ).…”
Section: Introductionmentioning
confidence: 99%